The Lost Book of Eleanor Dare : a novel - Brock, Kimberly (Nashville : Harper Muse, 2022)
"Based on real history and alternating between the story of war widow Alice searching for identity in the 1940s and excerpts from Eleanor Dare's Commonplace Book and the tale of her harrowing survival, The Lost Book of Eleanor Dare explores the meaning of female history and the sacrifices every mother makes for her daughter"--.
new book 2022 spring.
Keywords: FICTION / Southern; FICTION / Historical / World War II; United States -- History -- 20th century -- Fiction; Roanoke Island (N.C.) -- History -- 16th century -- Fiction; Roanoke Colony -- Fiction; Historical fiction